Analysis of Multiple Infection in Ixodic Ticks Dermacentor reticulatus in a Combined Natural Focus of Vector-Borne Infections in the Tomsk Region - O. V. Voronkova; V. N. Romanenko; A. V. Simakova; I. E. Esimova; D. A. D’yakov; E. A. Motlokhova; N. A. Chernyshov; D. M. Yamaletdinova (Проблемы особо опасных инфекций, 2023)
The aim of the study was to characterize mono- and mixed infection with causative agents of vector-borne infections in Dermacentor reticulatus ticks inhabiting one of the anthropourgic foci of the Tomsk Region. Materials and methods. D. reticulatus ticks were collected from vegetation “on the flag” in the forest park zones of the southern part of Tomsk in August and September, 2020–2021. To isolate nucleic acids from homogenates of mites and subsequent PCR diagnostics, kits of the RealBest series (“Vector-Best”, Novosibirsk) were used. 184 individual samples of nucleic acids were examined for the presence of molecular-genetic markers of tick-borne encephalitis virus (TBEV), pathogenic borrelia, babesia, rickettsia, anaplasma, and ehrlichia. Results and discussion. The spectrum of pathogens detected through PCR assay of ticks collected in one of the anthropurgic foci of the Tomsk Region in 2020 and 2021 includes TBEV, pathogenic borrelia, rickettsia, and babesia. The highest rate of D. reticulatus infection has been established in relation to candidate pathogens of tick-borne rickettsioses (Rickettsia sp.) and babesioses (Babesia sp.). The overall frequency of co-infection in D. reticulatus was 12.88 %. Seven different associations of pathogens infecting D. reticulatus have been identified. The majority (88.24 %) of the detected cases of mixed infection were rickettsia associations. Double infection has been registered in 94 % of the total number of mixed variants. Markers of four tick-borne infection pathogens simultaneously (Rickettsia species DNA, Babesia species DNA, Borrelia burgdorferi s.l. DNA and TBEV RNA) have been found in one sample. Changes in areal of the D. reticulatus against the background of an increase in their numbers, determines the need to analyze the epidemiological significance of the ticks of this species in combined foci of tick-borne infections, especially in the zone of sympatry with ixodic ticks of other species.